PSYCHOLOGICAL READINESS OF FUTURE LEGAL SPECIALISTS TO PROFESSIONAL SELFDETERMINATION - Tetiana L. Shepelenko (Alfred Nobel University Publisher, 2019)
The improvement of the quality of the professional training of future lawyers essentially depends on a well-founded and conscious professional self-determination, which in psychology is considered as a process of analyzing the internal resources of the individual, the skills of a future specialist and comparing its results with the requirements of the profession in the context of an independent choice of professional activity. The basic determinant of professional self-determination is psychological readiness as a complex dynamic structure, a set of intellectual, emotional, motivational and volitional aspects of the human psyche in their interrelation with external conditions. Psychological readiness as an integrated psychological education is a complex system of mutually determined structural and functional components, the main among which are: content, cognitive-operational, emotional-volitional, personal, appraisal ones. Psychological readiness for professional self-determination is caused to a significant measure by the development of substantive content and features of legal activities of future lawyers, which involves mastering general theoretical, special legal and psychological knowledge, skills and abilities. Psychological readiness for professional self-determination is connected with the professional orientation of cognitive processes, which requires their formation in accordance with the objective requirements of the legal profession. The basis of professional self-determination is motivation-value readiness, which determines the effectiveness of professional self-determination of future lawyers. Legal activity is often associated with the performance of official duties in extreme, stressful conditions, often leads to neuropsychic overload, which can cause steady states of emotional tension in an employee. Psychological readiness to reduce emotional tension requires the formation of lawyer's emotional and volition spheres, ensuring the state of mobilization of internal forces and readiness for action. Psycho- Psychological readiness is determined by the self-esteem that allows to be critical of oneself, to change the idea of "I am professional". Psychological readiness must also be considered at the level of compliance of the per- Psychological readiness must also be considered at the level of compliance of the per Psychological readiness must also be considered at the level of compliance of the personal and professional qualities of a lawyer with the objective requirements of the profession. Sufficient formation of all components of psychological readiness for professional self-determination, their close interconnection and intersectionality provides the adequate choice of a profession appropriate to the personality characteristics, and serves as a determining prerequisite for successful occupation and the means of effective further legal activity.